The C-seal trial: colorectal anastomosis protected by a biodegradable drain fixed to the anastomosis by a circular stapler, a multi-center randomized controlled trial - Bakker, Ilsalien S (BioMed Central, 2012)
BACKGROUND: Anastomotic leakage is a major complication in colorectal surgery and with an incidence of 11% the most common cause of morbidity and mortality. In order to reduce the incidence of anastomotic leakage the C-seal is developed. This intraluminal biodegradable drain is stapled to the anastomosis with a circular stapler and prevents extravasation of intracolonic content in case of an anastomotic dehiscence. The aim of this study is to evaluate the efficacy of the C-seal in reducing anastomotic leakage in stapled colorectal anastomoses, as assessed by anastomotic leakage leading to invasive treatment within 30 days postoperative. METHODS: The C-seal trial is a prospective multi-center randomized controlled trial with primary endpoint, anastomotic leakage leading to re-intervention within 30 days after operation. In this trial 616 patients will be randomized to the C-seal or control group (1:1), stratified by center, anastomotic height (proximal or distal of peritoneal reflection) and the intention to create a temporary deviating ostomy. Interim analyses are planned after 50% and 75% of patient inclusion. Eligible patients are at least 18 years of age, have any colorectal disease requiring a colorectal anastomosis to be made with a circular stapler in an elective setting, with an ASA-classification < 4. Oral mechanical bowel preparation is mandatory and patients with signs of peritonitis are excluded. The C-seal student team will perform the randomization procedure, supports the operating surgeon during the C-seal application and achieves the monitoring of the trial. Patients are followed for one year after randomization en will be analyzed on an intention to treat basis. DISCUSSION: This Randomized Clinical trial is designed to evaluate the effectiveness of the C-seal in preventing clinical anastomotic leakage. TRIAL REGISTRATION: NTR3080